Electrophysiological properties of layer 2/3 pyramidal neurons in the primary visual cortex of a retinitis pigmentosa mouse model (rd10) - Halfmann, Claas; Rüland, Thomas; Müller, Frank; Jehasse, Kevin; Kampa, Björn M. (Frontiers in Cellular Neuroscience, 2023)
Retinal degeneration is one of the main causes of visual impairments and blindness. One group of retinal degenerative diseases, leading to loss of photoreceptors, is collectively termed retinitis pigmentosa. In this group of diseases, the remaining retina is largely spared from initial cell death making retinal ganglion cells an interesting target for vision restoration methods. However, it is unknown how downstream brain areas, in particular the visual cortex, are affected by the progression of blindness. Visual deprivation studies have shown dramatic changes in electrophysiological properties of visual cortex neurons, but changes on a cellular level in retinitis pigmentosa have not been investigated yet. Therefore, we used the rd10 mouse model to perform patch-clamp recordings of pyramidal neurons in layer 2/3 of the primary visual cortex to screen for potential changes in electrophysiological properties resulting from retinal degeneration. Compared to wild type C57BL/6 mice, we only found an increase of intrinsic excitability around the time point of maximal retinal degeneration. In addition, we saw an increase in current amplitude of spontaneous putative inhibitory events after longer progression of retinal degeneration. However, we did not observe a long-lasting shift in excitability after prolonged retinal degeneration. Together, our results provide evidence of an intact visual cortex bearing promising potential for future therapeutic strategies to restore vision.